Pengaruh Daya Tarik Wisata, Kualitas Pelayanan dan Harga terhadap Niat Berkunjung Ulang di Wisata Pacet Mini Park Mojokerto - Muhammad Labib RIfqi (CV. Satria Jaya, 2023)
This purpose of this study is to understand the influence of Tourist attraction, Quality service, and Price on Intent to revisit at pacet mini park mojokerto.This research was quantitative research. The research population was pacet mini park mojokerto visitors. This research used sampling technique without certain considerations (Accidental Sampling) to get 100 respondents who made purchases at pacet mini park mojokerto based on age, occupation, and gender. The method of data collection used the questionnaires, observation, and documentations. The method of data analysis used the multiple regression analysis. The result of this research showed that the Tourist attraction, Quality service, and Price simultaneously have significant effect on the Intent to revisit. And partially Tourist attraction, Quality service, and Price have significant effect on the Intent to revisit. The Tourist attraction, Quality service, and Price on Intent to revisit in pacet mini park mojokerto visitors (Adjisted R Square) was 49%.